Benzodiazepines induced stupor in a four-year-old child: when EEG meets toxicology - Eva Montanari; Sabrina Siliquini; Alfredo Fabrizio Lo Faro; Maria Concetta Rotolo; Francesco Paolo Busardò; Raghvendra Kumar Vidua; Stefania De Simone; Angelo Montana (Egyptian Journal of Forensic Sciences)
Abstract Background The differential diagnosis of stupor is complex, especially in emergency settings. Idiopathic recurrent stupor, linked to the "endozepine-4" effect, must be considered, too. Stupor associated with endozepine has recently been questioned because more sophisticated toxicological tests have revealed that it is just an unreported exogenous exposure to benzodiazepines. Case presentation A four-year-old child in a stupor state was admitted to the Emergency Department. The EEG carried out during the state of stupor showed a typical pattern of acute drug abuse. Toxicological analyses revealed a high concentration of benzodiazepine, while second-level analyses identified both lorazepam and lormetazepam. Benzodiazepines chronic exposure was detected in unconventional matrices analysis, such as hair. It was an acute lorazepam and lormetazepam intoxication in a chronic tox history. Conclusions Should a patient in a stupor show up in an emergency, it becomes of primary importance to perform EEG and high-sensibility toxicological tests. Once the acute intoxication has been resolved, it is essential to analyze alternative matrices, such as hair, to reconstruct the patient's previous tox history. This suggestion is highly recommended in case of children. Chronic benzodiazepine intoxication may be a manifestation of chronic abuse, especially when directed towards children.